Operando investigation on the fast two-phase transition kinetics of LiFePO4/C composite cathodes with carbon additives for lithium-ion batteries - Shih, Jengywan; Lin, Guanyin; James Li, Ying Jeng; Hung, Tai-Feng; Jose, Rajan; Karuppiah, Chelladurai; Yang, Chun–Chen (Elsevier Ltd, 2022)
In this study, we demonstrate the effect of adding one-dimensional (1D) vapor-grown carbon fiber (VGCF) as a carbon additive to increase the electronic conductivity of LiFePO4 cathode. Because, the 1D VGCF structure can provide rapid and long-pathways for electron transfer and regulate a better phase transition effect on LiFePO4 cathode compared to the other-dimensional carbon additives. Here, the olivine-type LiFePO4/C composite (LFP/C) cathode is basically derived from a sol-gel method, followed by a spray-dry technique to obtain a homogenous spherical morphology. The carbon additives of 0D super P, 1D VGCF and 2D or 3D porous reduced graphene oxide (PGO) nanosheets containing cathodes-based, such as bare LFP/C, LFP/C/VGCF and LFP/C/PGO, half-cells were fabricated and tested at a cut-off voltage of 2.0 – 3.8 V (vs. Li/Li+). Interestingly, the LFP/C/VGCF showed better performance than the bare LFP/C and LFP/C/PGO. Especially at high-rate cycle-life, the LFP/C/VGCF cathode attained capacity retention of 100% for 100 cycles at 1C/1C and 98.83% for 100 cycles at 1C/10C. It is due to the higher electronic conductivity (ca. 2.36 × 10−4 S cm−1) and Li+ ion diffusion coefficient (ca. 2.56 × 10−13 cm2 s−1) of LFP/C/VGCF cathode than the other electrodes. It can also provide better reversibility in a phase transition of LiFePO4/FePO4 phases during the charge/discharge cycle, further confirmed by in-situ XRD and micro-Raman techniques. The results indicated that the LFP/C/VGCF cathode displayed much faster kinetics behavior than bare LFP/C cathode.